Educational Activities of Russian Missionaries in Syria 1840-1914 (Journal of the College of Basic Education, 2025)
The Russian Orthodox missionaries helped to revive the nationalist spirit in the Arab East region through their contribution to teaching the Arabic language in its schools and Arabizing many sources, in addition to their interest in Arab history and the emergence of the Orientalist movement and what it provided to the Arabs. Many missionaries also gave lectures and held seminars in which they explained the disadvantages of Ottoman rule, although this was only for the sake of Russia’s political interests, but it contributed to the awareness of the Arab people and their national cause. Graduates of missionary schools contributed to the formation of Arab associations, and these actions were reflected in Ottoman-Russian relations, as the Ottomans were not reassured by the presence of Russian missionaries on their lands because they were fully aware of the true goals of those campaigns and their description by the Russian government. However, these expeditions failed at the end of the nineteenth century due to the lack of financial resources for their goals of reaching the Black Sea, and the strength of competitors from Catholic and Protestant missionary societies supported by the rich countries of Europe.